Enhanced active oxidative species generation over Fe-doped defective TiO2 nanosheets for boosted photodegradation. Issue 67 (9th November 2020) - Gao, Xintong; Zhang, Shuai; Liu, Jingchao; Xu, Shiqi; Li, Zenghe
Abstract : Defect-rich ultrathin TiO2 nanosheets with tunable Fe doping realize the efficient generation of active oxidative species for boosted dye/antibiotic photodegradation. Abstract : Semiconductor photocatalysis is widely proposed for decomposing multiple pollutants via photo-generated oxidative species. However, the photocatalytic degradation performance in practical settings still remains unsatisfactory due to the limited production of active oxidative species (AOS). In this work, a defect engineering strategy was developed to explore the superiority of oxygen vacancies (Vo) and their structural regulation to enhance AOS production for boosting photodegradation. Taking anatase TiO2 as a model photocatalyst, ultrathin TiO2 nanosheets containing abundant Vo and appropriate Fe doping exhibited an unprecedented 134 times higher activity in the degradation of Rhodamine B (RhB) (rate as high as 0.3073 min −1 ) than bulk anatase and were superior to most reported photocatalysts. The defect-rich ultrathin TiO2 nanosheets could be further applied in high-efficiency degradation of tetracycline hydrochloride (TC-HCl) with the degradation rate of 0.0423 min −1 . The in situ electron paramagnetic resonance, advanced spectroscopic characterization and electrochemical measurement revealed the key role of Vo and Fe doping in facilitating the production of photo-generated holes and superoxide radicals (˙O2 − ) that were identified to be effective to decompose both RhB and TC-HCl. This research provides insight into defect engineering promoting AOS generation and gives inspiration for the design of efficient photocatalysts for photooxidation applications.